Annual Report on Exchange Arrangements and Exchange Restrictions 2003. (Annual Report on Exchange Arrangements and Exchange Restrictions; 2003, 2003)
This 2003 Annual Report on Exchange Arrangements and Exchange Restrictions provides a detailed description of the exchange arrangements and exchange/trade restrictions of individual IMF member countries and Hong Kong Special Administrative Region, as well as Aruba and the Netherlands Antilles. The report highlights that Bangladesh Bank announces a buying-selling rate band for the U.S. dollar against the taka for its transactions with authorized dealer banks. Trends of the real effective exchange rate of the taka against a trade-weighted basket of currencies of major trade partners are analyzed to monitor the external competitiveness of the exchange rate.